2016
DOI: 10.1016/j.celrep.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Dis3l2-Mediated Decay Is a Quality Control Pathway for Noncoding RNAs

Abstract: SUMMARY Mutations in the 3′-5′ exonuclease DIS3L2 are associated with Perlman syndrome and hypersusceptibility to Wilms’ tumorigenesis. Previously, we found that Dis3l2 specifically recognizes and degrades uridylated pre-let-7 microRNA. However, the widespread relevance of Dis3l2-mediated decay of uridylated substrates remains unknown. Here we applied an unbiased RNA immunoprecipitation strategy to identify Dis3l2 targets in mouse embryonic stem cells. The disease-associated long noncoding RNA (lncRNA) Rmrp, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
152
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(167 citation statements)
references
References 60 publications
(79 reference statements)
13
152
2
Order By: Relevance
“…In contrast, DIS3 knockdown led to a decrease in Y RNA levels (ϳ30% for Y1 and ϳ20% for Y3) and DIS3L2 knockdown had no significant effect on Y RNA levels. This is in contrast to recent reports that suggest that DIS3L2 targets 3=-uridylated Y RNAs for degradation (36,37), although as discussed below, we found that only a small fraction of Y RNAs are uridylated in HeLa cells. Moreover, DIS3L coknockdown with PARN is sufficient to rescue Y RNA levels to control, suggesting that DIS3L is responsible for Y RNA degradation when PARN is limiting (Fig.…”
contrasting
confidence: 55%
“…In contrast, DIS3 knockdown led to a decrease in Y RNA levels (ϳ30% for Y1 and ϳ20% for Y3) and DIS3L2 knockdown had no significant effect on Y RNA levels. This is in contrast to recent reports that suggest that DIS3L2 targets 3=-uridylated Y RNAs for degradation (36,37), although as discussed below, we found that only a small fraction of Y RNAs are uridylated in HeLa cells. Moreover, DIS3L coknockdown with PARN is sufficient to rescue Y RNA levels to control, suggesting that DIS3L is responsible for Y RNA degradation when PARN is limiting (Fig.…”
contrasting
confidence: 55%
“…Interestingly, many ncRNAs are protected from this degradation by structures such as stem loops (X. Liu et al, ). These studies suggest that mRNA decay is important for making sure the death program passes the “point of no return.” In non‐apoptotic cells, this pathway of TUTases and DIS3L2 act in quality control pathways of mRNAs and ncRNAs (Pirouz, Du, Munafò, & Gregory, ; Ustianenko et al, ). In contrast to the destabilizing effect of terminal uridyl, a more recent report has identified promiscuous nucleotidyl transferase activity leading to guanylation of the poly(A) tail that protects mRNAs from degradation (Chang et al, ; Y. Lim et al, ).…”
Section: Non‐polyadenylate 3′ End Modifications and Epitranscriptomicsmentioning
confidence: 99%
“…Uridylation‐mediated RNA degradation is definitely among the crucial functions of uridylation. Notably, a uridylation‐ and Dis3L2‐mediated surveillance pathway is key for the degradation of defective noncoding RNAs . Uridylated misprocessed transcripts were also detected in human mitochondria raising the possibility that uridylated‐mediated RNA surveillance might also operate in this organelle .…”
Section: Resultsmentioning
confidence: 99%
“…As Pol III terminates transcription following the synthesis of a short stretch of uridines, unprocessed transcripts may be targeted directly by Dis3L2 after export to the cytosol. However, TUT4/7 definitely assists Dis3L2 mediated‐degradation by synthesizing short oligouridine tails, mostly at positions close to stable secondary structures (Figure (e)) . An elegant experiment based on the decay rate analysis of randomized terminal sequences confirmed that a short stretch of terminal uridines significantly enhances degradation by the Drosophila Dis3L2 …”
Section: Uridylation Represses the Mirtron Pathwaymentioning
confidence: 93%
See 1 more Smart Citation